Comparative genomic analyses of the clinically-derived Winkia strain NY0527: the reassignment of W. neuii subsp. neuii and W. neuii subsp. antitratus into two separate species and insights into their virulence characteristics - Cai, Xunchao; Peng, Yao; Li, Meng; Qiu, Yifeng; Wang, Yuhan; Xu, Long; Hou, Qi (Frontiers in Microbiology, 2023)
Background Winkia neuii, previously known as Actinomyces neuii, is increasingly recognized as a causative agent of various human infections, while its taxonomy and genomic insights are still understudied. Methods A Winkia strain NY0527 was isolated from the hip abscess of a patient, and its antibiotic susceptibility was assessed. The genome was hybrid assembled from long-reads and short-reads sequencing. Whole-genome-based analyses on taxa assignment, strain diversity, and pathogenesis were conducted. Results The strain was found to be highly susceptible to beta-lactam antibiotics, but resistant to erythromycin, clindamycin, and amikacin. The complete genome sequences of this strain were assembled and found to consist of a circular chromosome and a circular plasmid. Sequence alignment to the NCBI-nt database revealed that the plasmid had high sequence identity (>90%) to four Corynebacterium plasmids, with 40–50% query sequence coverage. Furthermore, the plasmid was discovered to possibly originate from the sequence recombination events of two Corynebacterium plasmid families. Phylogenomic tree and genomic average nucleotide identity analyses indicated that many Winkia sp. strains were still erroneously assigned as Actinomyces sp. strains, and the documented subspecies within W. neuii should be reclassified as two separate species (i.e., W. neuii and W. anitratus). The core genome of each species carried a chromosome-coded beta-lactamase expression repressor gene, which may account for their broadly observed susceptibility to beta-lactam antibiotics in clinical settings. Additionally, an ermX gene that expresses fluoroquinolone resistance was shared by some W. neuii and W. anitratus strains, possibly acquired by IS6 transposase-directed gene transfer events. In contrast, tetracycline resistance genes were exclusively carried by W. neuii strains. In particular, W. neuii was found to be more pathogenic than W. anitratus by encoding more virulence factors (i.e., 35–38 in W. neuii vs 27–31 in W. anitratus). Moreover, both species encoded two core pathogenic virulence factors, namely hemolysin and sialidase, which may facilitate their infections by expressing poreformation, adhesion, and immunoglobulin deglycosylation activities. Conclusion This study highlights the underappreciated taxonomic diversity of Winkia spp. and provides populational genomic insights into their antibiotic susceptibility and pathogenesis for the first time, which could be helpful in the clinical diagnosis and treatment of Winkia spp. infections.